An ex vivo Human Skin Model to Study Superficial Fungal Infections - Corzo-León, Dora E.; Munro, Carol A.; MacCallum, Donna M. (Frontiers in Microbiology, 2019)
Human skin fungal infections (SFIs) affect 25% of the world’s population. Most of these infections are superficial. The main limitation of current animal models of human superficial SFIs is that clinical presentation is different between the different species and animal models do not accurately reflect the human skin environment. An ex vivo human skin model was therefore developed and standardised to accurately model SFIs. In this manuscript, we report our protocol for setting up ex vivo human skin infections and report results from a primary superficial skin infection with Trichophyton rubrum, an anthropophilic fungus. The protocol includes a detailed description of the methodology to prepare the skin explants, establish infection, avoid contamination, and obtain high quality samples for further downstream analyses. Scanning electronic microscopy (SEM), histology and fluorescent microscopy were applied to evaluate skin cell viability and fungal morphology. Furthermore, we describe a broad range of assays, such as RNA extraction and qRT-PCR for human gene expression, and protein extraction from tissue and supernatants for proteomic analysis by liquid chromatography-mass spectrometry (LC-MS/MS). Non-infected skin was viable after 14 days of incubation, expressed genes and contained proteins associated with proliferative, immune and differentiation functions. The macroscopic damage caused by T. rubrum had a similar appearance to the one expected in clinical settings. Finally, using this model, the host response to T. rubrum infection can be evaluated at different levels.